A emergência dos contos de fadas infantis: processos históricos e procedimentos literários envovidos - Vieira, Samela Roberta de Lima (Brasil, 2023)
This bibliographic research aims to understand the emergence of children's fairy tales, which are the first narratives presented to children due to their educational potential. The birth of Children's Literature is attributed to the book "Mother Goose Tales" published by Perrault in 1695. However, these stories already existed in the form of popular oral narratives during the Middle Ages, without being specifically intended for children and containing content that may be considered inappropriate nowadays. The discussion seeks to answer the following problem: What were the historical processes that made the emergence of fairy tales possible? And what procedures did the folk tales undergo to become works of Children's Literature? The work is structured into two chapters. In the first chapter, we highlight the emergence of the book and the emergence of childhood as historical processes that intertwine and favor the appearance of Children's Literature. In the second chapter, guided by Perrault's work, we study the procedures that folk tales underwent to become literary children's tales.